The impact of a good season start on team performance in elite handball - Lago-Penas, C.; Fernandez-Villarino, M. A.; Gonzalez-Garcia, I.; Sanchez-Fernandez, P.; Sampaio, J. (Journal of Human Kinetics, 2016)
The aim of the current study was (i) to identify how important was a good season start in relation to elite handball teams` performance, and (ii) to examine if this impact was related to the clubs` financial budget. The match performances and annual budgets of all teams were collected from the Spanish Professional Handball League during ten seasons. The dependent variable was the difference between the ranking of each team in accordance to the annual budget and the ranking of each team at the end of the season. A k-means cluster analysis classified the clubs according to their budget as High Range Budget Clubs (HRBC), Upper-Mid Range Budget Clubs (UMRBC), Lower-Mid Range Budget Clubs (LMRBC) and Low Range Budget Clubs (LRBC). Data were examined through linear regression models. Overall, the results suggested that the better the team performance at the beginning of the season, the better the ranking at the end of the season. Each position in the ranking above expected in accordance to the budget of the teams in Rounds 3, 4 or 5 improved by 0.47, 0.50 or 0.49, respectively, in the ranking at the end of the season (p<0.05). However, the impact of the effect depended on the clubs` annual budget. For UMRBC, LMRBC and LRBC a good start to the season had a positive effect on the final outcome (p<0.05). Nevertheless, for HRBC, a good or a bad start of the season did not explain their final position. These variables can be used to develop accurate models to estimate final rankings. UMRBC, LMRBC and LRBC can benefit from fine-tuning preseason planning in order to accelerate the acquisition of optimal performances.